Lower dosage of aspirin promotes cell growth and osteogenic differentiation in murine bone marrow stromal cells - Mi Du; Wan Pan; Xiaoqi Duan; Pishan Yang; Shaohua Ge (Elsevier, 2016)
Background/purpose: The effect of aspirin on bone regeneration remains controversial. This study aimed to determine the effect of various concentrations of aspirin on cell viability, osteogenic differentiation, cell cycle, and apoptosis on ST2 cells to find an effective range of aspirin for bone regeneration induction. Materials and methods: Cell viability was measured with MTT assay after being stimulated with aspirin for 1 day, 2 days, 3 days, 5 days, and 7 days. Alkaline phosphatase (ALP) activity was measured after cells were treated for 1 day, 3 days, and 7 days. Expression of runt-related transcription factor 2 (Runx-2) was evaluated using Western-blot analysis at 3 days and 7 days. Flow cytometry was used for cell cycle and apoptosis measurement after cells were treated for 48 hours. Results: Lower concentrations of aspirin (1μΜ and 10μM) promoted cell growth and increased ALP levels and Runx-2 expression, while higher concentrations (100μΜ and 1000μΜ) inhibited cell growth (P < 0.05), and lost their effect on ALP activity after 3 days, while even showing an inhibitory effect on the expression of Runx-2. Aspirin at a concentration of 100μM promoted cell mitosis from the S phase to the G2/M phase, and 1000μM arrested the cell cycle in the resting phase G0/G1 (P < 0.05). Parallel apoptosis/necrosis studies showed the percentage of cells in apoptosis decreased dramatically at any dose of aspirin. Conclusion: A lower dosage of aspirin could promote ST2 cell growth, osteogenic differentiation, and inhibit their apoptosis which indicates that aspirin can be used as an alternative for bone regeneration.